Matters of testimony : interpreting the scrolls of Auschwitz - Chare, Nicholas 19XX- (Berghahn Books, 2016)
Introduction: matters of testimony -- Matters of history -- Zalman Gradowski: literature in the death factory -- Scattered selves: the stories of Leyb Langfus -- Final arrangements: Zalman Lewental's histories of resistance -- Characters and letters: Chaim Herman and Marcel Nadjary -- The camera eye: four photographs from Birkenau -- Conclusion: crossing the circle of flame